A Historiographic Review: The Bulgarian Scholars on the Churches of the Second Bulgarian Kingdom - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2019)
The article deals with the history of the study of church architecture in various regions of the Second Bulgarian Kingdom (1186–1396) on the material of the most significant monuments of such regions as Nessebar, Sozopol, Cherven, Shumen, Veliko Turnovo and Asenovo, etc. An attempt is made to analyze the main bibliography on the topic and present various points of view of Bulgarian authors regarding the specific features and significance of the churches of the period in question.
Keywords: Second Bulgarian Kingdom; medieval Bulgarian architecture; Byzantine architecture